Do social network sites contribute for building brands? Evaluating the impact of users’ participation on brand awareness and brand attitude - Langaro, D.; Rita, P.; Salgueiro, M. F. (Journal of Marketing Communications, 2018)
Social networking sites (SNSs) have attracted increasing attention from brands, which look at the platform as a privileged communication channel to reach their audiences. Despite their growing adoption, few research efforts have been devoted to evaluate SNSs' concrete implications for the brands. The current study addresses this opportunity, proposing a model that evaluates the impact of users' participation in SNSs on brand awareness and brand attitude, the two main pillars of brand knowledge. The study focuses on brand like pages in Facebook, the most used SNSs platform for brands. An online quantitative survey with brand like page users of leading brands in Facebook was implemented. Confirmatory factor analysis was used to estimate the measurement model and structural equation modelling was used to test the proposed research hypotheses. The results identify a significant, positive and direct impact of users' participation on brand awareness. Brand attitude also substantially benefits from users' participation, but this relationship is mediated by brand awareness. The findings help to validate SNSs' significant role on building brand knowledge and to position users' participation at the core of brands' SNSs objectives. Furthermore, the study provides a practical research framework, easily adapted for monitoring purposes and managerial guidance. Future research directions are discussed.